The role of professional commitment on rationalization tendency of earning management: an experimental study - Septiari, Dovi; Dwita, Sany; Honesty, Helga Nuri (Asian journal of business ethics, 2023)
This study investigates the role of advantageous comparisons and professional commitment in earning management rationalization. Our study adopted a laboratory between-subject experimental design with 139 accounting students. The results show that advantageous comparisons and professional commitment affect the rationalization of earning management actions. Moreover, compared to participants with high levels of professional commitment, those with low levels of professional commitment view earning management as a more appropriate action when they are engaged in earning management and viewing the egregious example of that action. This finding is important because it explains how personal psychological factors affect the ethical cognitive processes of accountants. This study complements the lack of previous studies and argues that the propensity to compare acts of delinquency depends on an individual's commitment to their profession. We also emphasize the importance of investigating this issue outside of the US context. The results of this study may be helpful to managers, practitioners, academics, and accounting researchers with a better understanding of the potential impact of exposure to earning management practices and an individual’s professional commitment to earning management behaviour. Further, based on this study, all stakeholders may be better positioned to suggest possible remedies and mitigate these behaviours.